Disease and Patient Characteristics Contributing to Diagnostic Delays in Patients With Guillain-Barré Syndrome - Pathikonda, Chakrapani; Katyal, Nakul; Narula, Naureen; Govindarajan, Raghav (Frontiers in Neurology, 2021)
Introduction: Diagnosis of Guillain Barre syndrome (GBS) is often made clinically. Certain patient and disease characteristics can cause delays in diagnosis and management. Methods: Observational retrospective study of forty-four patients diagnosed with GBS either clinically, cerebrospinal fluid analysis, and/or by electro-diagnostic criteria at a teaching hospital (University of Missouri Hospital) in Columbia, Mid-Missouri between 2011 and 2017. Results: Patients with coexisting neurological conditions had statistically significant delay in diagnosis of GBS (Mean (SD); 13 +/- 5 vs 9.39 +/-4.7; p=0.03). Patients presenting with motor + symptoms (sensory and/or autonomic, in addition to motor), compared to those with only motor symptoms had statistically significant delay in diagnosis of GBS (Mean (SD); 11.90 +/- 5 vs 8.58 +/-4; p=0.04). Discussion: Presence of co-existing neurological conditions, and motor+ symptoms can delay timely diagnosis and management of GBS.